(untitled) (De Musica, 2022)
Don Giovanni is one of the best-known works of Mozart’s production created a short distance from Mozart’s entry into Freemasonry. The vision of the East changes hand in hand with the growth of oriental knowledge, and Mozart does not remain a stranger, as evident from many aspects of Don Giovanni. The psychology of the characters is intertwined, for Kierkegaard, in the philosophy of narration that represents sensual genius; he justifies it, draws from it a demonic dimension of Don Giovanni while Goethe finds it in the creative thrust of the composer. This study wants to highlight how much Masonic morality is permeated in the work but also, and above all, an oriental dimension directed to the circular karmic vision of saṃsāra which is represented precisely by the desire of desire and which pushes the protagonist to never interrupt this flow of seduction. The non-interruption of this circularity will lead him to spiritual involution and to the world of the underworld.